2004
DOI: 10.1097/01.cco.0000129679.49651.50
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract neoplasms: update 2003

Abstract: Biliary tract neoplasm remains one of the most aggressive malignancies. However, as for other gastrointestinal malignancies, biological studies and diagnostic and therapeutic improvements have provided interesting results that could lead to a major improvement in the prognosis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 71 publications
(17 reference statements)
0
26
0
6
Order By: Relevance
“…1,2 In this context, the survival rate is as high as 85-100% at 5 years for lesions limited to the muscle layer. 2 Nevertheless, even after extensive surgery, a considerable number of patients with stage II-IV gallbladder carcinoma develop distant or intraabominal metastases that are resistant to conventional chemotherapy. 2 Sequential morphological alterations from precancerous dysplasia or adenoma to carcinoma have been regarded as models implicated in tumorigenesis of gallbladder carcinoma.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In this context, the survival rate is as high as 85-100% at 5 years for lesions limited to the muscle layer. 2 Nevertheless, even after extensive surgery, a considerable number of patients with stage II-IV gallbladder carcinoma develop distant or intraabominal metastases that are resistant to conventional chemotherapy. 2 Sequential morphological alterations from precancerous dysplasia or adenoma to carcinoma have been regarded as models implicated in tumorigenesis of gallbladder carcinoma.…”
mentioning
confidence: 99%
“…[1][2][3] The effective therapy to cure gallbladder carcinoma is complete surgical resection at the early stage, whereas most patients present with advanced disease and have few therapeutic options. 1,2 In this context, the survival rate is as high as 85-100% at 5 years for lesions limited to the muscle layer. 2 Nevertheless, even after extensive surgery, a considerable number of patients with stage II-IV gallbladder carcinoma develop distant or intraabominal metastases that are resistant to conventional chemotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of chemotherapy in cholangiocarcinoma is still not clear especially with the low response rates [5] , disappointing efficacy results and lack of a superior standard chemotherapeutic regimen [7,38] . Conflicting data exist regarding the role of chemotherapy in cholangiocarcinoma.…”
Section: Farhat Mh Et Al Prognosis In Cholangiocarcinomamentioning
confidence: 99%
“…Moreover, the majority of patients have frequent recurrences after the surgery, and pursue the chemotherapy or radiotherapy treatment when recurrences happened after the surgery (2,15). Several previous studies have demonstrated high risks of disease progression, using surgically-resected GBC cases, and histological grade, depth of wall infiltration, and lymph node status have been determined to be clinicopathological prognostic factors (6,22).…”
mentioning
confidence: 99%